A coupling system to predict the core and skin temperatures of human wearing protective clothing in hot environments. (November 2015) - Yang, Jie; Weng, Wenguo; Fu, Ming
Abstract: The aim of this study is to predict the core and skin temperatures of human wearing protective clothing in hot environments using the coupling system. The coupling system consisted of a sweating manikin Newton controlled by a multi-node human thermal model, and responded dynamically to the thermal environment as human body. Validation of the coupling system results was conducted by comparison with the subject tests. Five healthy men wearing protective clothing were exposed to the thermal neutral and high temperature environments. The skin temperatures of seven body segments and the rectal temperatures were recorded continuously. The predictions of core temperatures made by the coupling system showed good agreement with the experimental data, with maximum difference of 0.19 °C and RMSD of 0.12 °C. The predicted mean skin temperatures fell outside of the 95% CI for most points, whereas the difference between the simulated results and measured data was no more than 1 °C which is acceptable. The coupling system predicted the local skin temperatures reasonably with the maximum local skin temperature of 1.30 °C. The coupling system has been validated and exhibited reasonable accuracy compared with the experimental results. Highlights: A coupling system to predict the human core and skin temperatures was developed. Experiments were conducted in hot environment to get human temperatures. Comparison between the predicted results and experimental data was conducted. The coupling system has shown accurate compared with the experimental results.